Penguatan Kapasitas Konselor melalui Diseminasi Aplikasi “KONSELO” sebagai Multi-Platform Konseling Online Berbasis Sustainable Development Goals - Zadrian Ardi; Ilmiyati Rahmy Jasril; Frischa Meivilona Yendi; Soeci Izzati Adlya (Universitas Negeri Padang, 2024)
The second year of the P3UPT program for the KONSELO application focused on broader dissemination of the online counseling platform to all districts and cities in West Sumatra. This community service activity was implemented through a series of webinars, face-to-face workshops, Training of Trainers (ToT), and FGD-based application upgrading involving counselors affiliated with PD ABKIN West Sumatra and CV Rumah Konseling Handayani. The results showed a significant increase in counselors' ability to operate the KONSELO application, as well as strengthening the digital counseling service network to reach university students experiencing academic stress across West Sumatra. This activity also led to the development of a sustainable partner business scheme and improved financial management for partner institutions, thereby supporting the achievement of Sustainable Development Goals (SDGs), particularly in the domain of Good Health and Well-being.